ORIGIN OF LONG-CHAIN ALKYLCYCLOHEXANES AND ALKYLBENZENES IN A COAL-BED WAX - Ji-Zhou D.; Vorkink W.P.; Lee M.L. (My University, 1993)
A coal-bed wax was fractionated and analyzed using capillary column GC and combined GC/MS. It was found that the major components in the wax were n-alkanes (55.6%), cyclic/branched alkanes (26.0%), and several homologous series of alkylbenzenes (5.7%). All alkylbenzene isomers (except 6-n-alkyl-m-xylene) were positively identified by comparison with the retention times and mass spectra of newly synthesized authentic standards. 5-n-Alkyl-m-xylene, 2-n-alkyl-p-xylene, 4-n-alkyl-m-xylene, 4-n-alkyl-o-xylene, 2-n-alkyl-m-xylene, and 3-n-alkyl-o-xylene were identified for the first time from geological sources. All of these long-chain alkyl compounds (e.g., n-alkylcyclohexanes, n-alkylbenzenes, n-alkyl-o-toluenes, n-alkyl-p-toluenes, and 5-n-alkyl-m-xylenes) have similar total carbon number distributions and maxima with a slight even over odd carbon number preference between C28-C30. Moreover, the carbon number distributions of these compounds resembled those of the n-alkanes found in the same wax with slight odd over even carbon preference between C27-C31. This indicates that the alkylcyclohexanes and alkylbenzenes may have the same fatty acid precursors as the n -alkanes. The alkylcyclohexanes and alkylbenzenes could have been formed by direct cyclization and aromatization, while the n-alkanes could have been formed by decarboxylation of the straight chain fatty acids. This explanation is further supported by the identification of homologous series of tetramethyl-n-alkylbenzenes and pentamethyl-n-alkylbenzenes with relatively high abundances at C-15, C-16, and C18, and a fatty acid distribution with maxima at C-16 and C18. Based on these findings, mechanisms for the conversion of fatty acids or alcohols to alkylcyclohexanes and alkylbenzenes are proposed.